2019
DOI: 10.1177/0310057x19838765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posterior quadratus lumborum blockade on the quality of recovery after major gynaecological laparoscopic surgery: A randomized controlled trial

Abstract: Bilateral quadratus lumborum blockade (QLB) using ultrasound guidance has been introduced as an abdominal truncal block to improve postoperative analgesia and quality of recovery (QoR) after abdominal surgery, but efficacy remains controversial. The primary aim of this study was to evaluate the efficacy of posterior QLB on the postoperative QoR, and secondarily to evaluate postoperative pain after gynaecological laparoscopic surgery (LS). This study was a single-centre randomized controlled trial. QLB group pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…The QoR-40 quality of recovery inventory has recently started to be used to assess quality of early postoperative recovery in numerous studies. While different surgical and anesthetic techniques have been employed, the effectiveness of the analgesia method employed has been evaluated with QoR-40 quality of recovery inventory 15 , 16 . We also employed QoR-40 together with VAS scores, postoperative fentanyl consumption, and numbers of patients using rescue analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The QoR-40 quality of recovery inventory has recently started to be used to assess quality of early postoperative recovery in numerous studies. While different surgical and anesthetic techniques have been employed, the effectiveness of the analgesia method employed has been evaluated with QoR-40 quality of recovery inventory 15 , 16 . We also employed QoR-40 together with VAS scores, postoperative fentanyl consumption, and numbers of patients using rescue analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the patients should be informed of the possibility of both numbness and weakness as the potential side-effects in their preoperative consent. [ 27 ] In the present study, no patient reported any adverse events. Similarly, the pain assessment and patient satisfaction score done at three months postoperatively were similar in both the groups.…”
Section: Discussionmentioning
confidence: 42%
“…Although the pectoral nerve block improved pain score at 6 h postoperatively, the QoR-40 score on POD 1 was not improved. Fujimoto and colleagues [ 19 ] demonstrated no improvement in quality of recovery or postoperative analgesia for patients received single-shot posterior quadratus lumborum blockade (QLB) after laparoscopic gynecological surgery. The median QoR-40 score was 154 (133–168) in the QLB group and 158 (144–172) in the control group ( P = 0.361) respectively.…”
Section: Discussionmentioning
confidence: 99%